Internalization of religious moderation values in islamic boarding schools as an effort to face the era of society 5.0 - Dedi Ardiansyah (Balai Diklat Keagamaan Ambon, 2023)
In the context of technological developments, Islamic boarding schools need to form students who are moderate, tolerant, and adaptive to changing times. This study aims to analyze the process of internalizing the values ​​of religious moderation in Islamic boarding schools as an effort to face the Society 5.0 era. This research uses a literature study approach by collecting data from various relevant literature sources, such as books and journals related to the internalization of religious moderation values ​​in Islamic boarding schools. The data obtained was then analyzed descriptively to describe the process of internalizing the value of religious moderation and the benefits for Islamic boarding schools. The research results show that Islamic boarding schools have a central role in internalizing the values ​​of religious moderation. The implication of this research is the need to increase the role of Islamic boarding schools in developing activities that support the internalization of the values ​​of religious moderation.